Earthquake Resistant Assessment of Building Construction Technique in the Nayagaun Settlement of Kavre before Gorkha Earthquake - R. Pradhan; P.M Pradhan (International Association of Lowland Technology, 2020)
The major earthquake on April 25, 2015 (7.8 Mw) and theaftershock on May 12, 2015 (7.3 Mw) caused severe damages onthe Nayagaun settlement of Dhulikhel Municipality, Kavre. Thisstudy proposes to highlight the extent of damages in the buildingsdue to the absence of the earthquake resistant components. Inthis study, the suitability of the building construction techniques inthe study area has been addressed after knowing theconsequences faced due to the absence of the earthquakeresistant components in the buildings. This study provides idea onthe earthquake resistant components and its significance in theresidential buildings during the earthquake period. In this study,the types of the buildings damaged are tabulated according to thetypology of the buildings whereas the type of damages incurredare categorized based on the grade of damages (partiallydamaged or fully collapsed). Some mitigating measures areidentified throughout the study to overcome the futureearthquakes